2006
DOI: 10.1287/mnsc.1060.0597
|View full text |Cite
|
Sign up to set email alerts
|

Common Method Variance in IS Research: A Comparison of Alternative Approaches and a Reanalysis of Past Research

Abstract: Despite recurring concerns about common method variance (CMV) in survey research, the information systems (IS) community remains largely uncertain of the extent of such potential biases. To address this uncertainty, this paper attempts to systematically examine the impact of CMV on the inferences drawn from survey research in the IS area. First, we describe the available approaches for assessing CMV and conduct an empirical study to compare them. From an actual survey involving 227 respondents, we find that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
1,533
3
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,548 publications
(1,680 citation statements)
references
References 52 publications
25
1,533
3
20
Order By: Relevance
“…Lindell and Whitney (2001), Podsakoff et al (2003) and Malhotra, Kim, and Patil (2006) review several statistical methods that are more sophisticated than Harman's test, which can be used to test and possibly control for CMV. Different statistical remedies are available for different types of research settings and different sources of CMV.…”
Section: Remedies 3 and 4: Deal With CMV In Thementioning
confidence: 99%
See 1 more Smart Citation
“…Lindell and Whitney (2001), Podsakoff et al (2003) and Malhotra, Kim, and Patil (2006) review several statistical methods that are more sophisticated than Harman's test, which can be used to test and possibly control for CMV. Different statistical remedies are available for different types of research settings and different sources of CMV.…”
Section: Remedies 3 and 4: Deal With CMV In Thementioning
confidence: 99%
“…7 Note that a complete identification of all sources of CMV is not necessary. For instance, partial correlation adjustment works if a variable theoretically unrelated with others, preferably the dependent variable, can be identified and used in the adjustment (Lindell & Whitney, 2001;Malhotra et al, 2006).…”
Section: Notesmentioning
confidence: 99%
“…Usually, self-reports questionnaires (because self-report measures are supposed to be correlated), social desirability (it might inflate observed correlations), negative affectivity (respondent's negative emotions might bias the relationships in a negative direction), and acquiescence (the tendency to agree with the items no matter the content) are cited as most usual sources of common method variance. As result, several statistical procedures were developed to overcome this problem, such as the traditional MTMM matrix procedure, the CFA-based MTMM technique, Harman's single-factor test, and marker-variable technique (Malhotra, Kim and Patil, 2006).…”
Section: B Satisfaction With Rewards and Benefits Is The Amount Of Pmentioning
confidence: 99%
“…First, we compared a marker variable, unrelated to the variables in this study ("How involved are you in your firm's dealings with this supplier? "), and found it uncorrelated with all constructs in this study (Lindell and Whitney 2001;Malhotra et al 2006). We also used a confirmatory factor analysis approach to Harmon's one-factor test (Podsakoff et al 2003;Sanchez and Brock 1996).…”
Section: Sample and Data Collectionmentioning
confidence: 74%